1995
DOI: 10.1177/107110079501600603
|View full text |Cite
|
Sign up to set email alerts
|

Update on Women's Footwear

Abstract: Shoes have been implicated as being responsible for the majority of foot deformities and problems that physicians encounter in women. In our original study of 356 women, the majority of women studied wore shoes that were too small for their feet, had foot pain and deformity, and had increased in shoe size since the age of 20. The women without foot pain or deformities also wore shoes that were smaller than their feet but to a lesser degree. In the present study, data on 255 of the original 356 women are evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…High-heeled gaits induce changes in the soft tissues around the foot by increasing the shock loadings during static and dynamic movements and are considered to cause potentially damaging conditions such as deformations in the foot and ankle, weakening of muscles, and damages to ligaments and joints14, 15 ) . The body is affected greatly by these influences, and hence restricted leg movements during gait are seen.…”
Section: Discussionmentioning
confidence: 99%
“…High-heeled gaits induce changes in the soft tissues around the foot by increasing the shock loadings during static and dynamic movements and are considered to cause potentially damaging conditions such as deformations in the foot and ankle, weakening of muscles, and damages to ligaments and joints14, 15 ) . The body is affected greatly by these influences, and hence restricted leg movements during gait are seen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that incorrectly fitting footwear is strongly associated with forefoot pathology and foot pain [3,11]. Other studies have shown the effects of footwear on feet especially in women [12,13]. …”
Section: Resultsmentioning
confidence: 99%
“…(13,14) However, forefoot pain involving the toes and ball of foot (along the metatarsal heads) has a well-established association with ill-fitting footwear, especially in women wearing high-heeled shoes. (15)(16)(17) Poorly fitted shoes have been identified as the principal cause of common foot disorders in women, (7,18) although interestingly, the prevalence of foot problems is comparatively low in populations that do not wear shoes. (19,20) Apart from giving rise to short-term problems such as recurrent foot pain, long-term morbidities such as progressive forefoot deformities and accelerated degenerative disorders have been attributed to ill-fitting footwear.…”
Section: Discussionmentioning
confidence: 99%